2001
DOI: 10.1002/gcc.1117
|View full text |Cite
|
Sign up to set email alerts
|

Genetic imbalances in 26 cases of penile squamous cell carcinoma

Abstract: To obtain more information on chromosomal changes in the up-to-now poorly studied tumor class of penile squamous cell carcinoma (SCC), we performed a comparative genomic hybridization study of 26 cases of this rare tumor. DNA sequence copy number alterations (CNAs) very similar to those detected in other SCC types, such as oral and esophageal SCC, were noted. The most common copy number gains were found in 8q24, 16p11-12, 20q11-13, 22q, 19q13, and 5p15, and the most common deletions were detected in 13q21-22, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…8 In contrast, the gain of the 8q24 chromosomal band containing MYC is a recurrent finding in PSCC. 9 We focused on the detection of MYC aberrations in all stages of PSCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 In contrast, the gain of the 8q24 chromosomal band containing MYC is a recurrent finding in PSCC. 9 We focused on the detection of MYC aberrations in all stages of PSCC.…”
Section: Discussionmentioning
confidence: 99%
“…8 Comparative genomic hybridization technique in PSCCs demonstrated frequent copy number gains in 8q24, 16p11-12, 20q11-13, 22q, 19q13 and 5p15 with no clear correlation between tumor grade and chromosome aberrations. 9 MYC is a protooncogene located in the 8q24 chromosome band, encoding a transcription factor with a basic helix-loop-helix leucine zipper protein domain that appears to regulate cellular proliferation, differentiation and apoptosis. In vitro studies indicate that MYC is essential for the proliferation of most cell types.…”
mentioning
confidence: 99%
“…Soufir et al [25] suggested a mutation of p53 gene to have been observed in three of three cases (100%), Levi et al [15] in seven of 21 cases (33%), but both Castern et al [3] and Suzuki et al [27] suggested no mutation of p53 gene was observed. Alves et al [1] presented deletions in 13q21-22 and 4q21-32 on chromosome region and Poetsch et al [20] presented deletions in 2q,6p,8q, 9p, 21q, and 17p13 on chromosome region. For methylation, besides a few, only two literatures discussed PC.…”
Section: Discussionmentioning
confidence: 99%
“…No association to grade and stage was detected. The same authors [85] noted telomerase activity in 85.5% of invasive penile tumors. The possible prognostic value of these findings needs further clarification.…”
Section: Chromosomal Abnormalities and Prognosismentioning
confidence: 88%
“…Alves et al [85] showed that DNA sequence copy-number alterations were detected in penile SCC with distinct similarity to other SCC (oral and esophageal). In 23 tumors that were analyzed, common copy-number gains included 8q24, 16p11-12, 20q11-13, 22q, 19q13 and 5p15.…”
Section: Chromosomal Abnormalities and Prognosismentioning
confidence: 98%